New Contender in Networked Storage. - Paulson, Linda Dailey (Computer (00189162), 2007)
The articles discusses Coraid's advanced technology attachment over Ethernet (AoE) which is expected to compete with technologies such as Fibre Channel over IP and iSCSI in the networked-storage market. AoE lets users access information from or write data to standard PC storage drives via Ethernet networks, which Coraid is predicting will lower networked-storage costs. According to Coraid CEO Jim Kemp, the use of AoE will reduce the number of processing and connection issues, making it faster and simpler. Comparisons of AoE to its competitors are included in the article.